Pathogenesis of mixed infection by Spironucleus sp. and Citrobacter freundii in freshwater angelfish Pterophyllum scalare - Gallani, Sílvia U. [UNESP]; Sebastião, Fernanda de A. [UNESP]; Valladão, Gustavo M.R. [UNESP]; Boaratti, André Z. [UNESP]; Pilarski, Fabiana [UNESP] (Elsevier, 2016)
The present study was carried out to identify and describe the pathology of the freshwater angelfish Pterophyllum scalare during chronic mortality in an in-door aquaculture system. Scraping of the integument and gills and the collection of intestinal contents to search for external and internal parasites were performed. Kidneys were collected aseptically for the microbiological analysis and the isolates were subjected to antibiotics to test for susceptibility. Subsequently, necropsy for macroscopic assessment and collection of internal organs for histopathology were performed. The fish exhibited lethargy, lip tumor, hemorrhage and liver granuloma. No ectoparasites were diagnosed. Endoparasites of the genus Spironucleus were found in large numbers in the intestine of the affected fish. In the microbiological analysis, Citrobacter freundii was isolated from the kidney and identified by colony PCR. This bacterium showed susceptibility to three of the eight antibiotics evaluated: ciprofloxacin, cefoxitin and tetracycline. For the pathological analysis, liver and spleen granulomas were present. In the intestinal tissue, a large and unusual amount of mast cells and their free granules were described and discussed in detail. The present study showed that mast cells play an important role during the chronic infection of freshwater angelfish.
Keywords: Aquaculture; Aquarium; Bacteria; Disease; Ornamental; Parasite